Passive hemagglutination test for measles immunity and serodiagnosis. - Sakata, H (1988)
A passive hemagglutination (PHA) test for measles was evaluated in comparison with hemagglutination inhibition (HI) and neutralization (NT) tests. The PHA test determines exclusively the level of antibody directed to the hemagglutinin protein of measles virus. The ratio of PHA to HI titer was 1 to 32 (geometric mean, 6.5) for the first 5 weeks of infection but declined to near unity thereafter. It gradually increased again to 4 to 32 (geometric mean, 11.7) over several years. The initial high PHA titer relative to the HI titer was most likely due to the presence of the immunoglobulin M antibody known to be efficient in agglutination, because 2-mercaptoethanol (2ME) treatment of sera reduced the PHA titer to a level similar to that of the HI titer. The PHA titer in sera obtained after the convalescent phase was insensitive to 2ME, and the relative increase in the PHA over the HI titer was presumably a result of increased antibody avidity. In some individuals, the HI titer fell to below detectable levels several years after either natural infection or vaccination, but the PHA as well as the NT titer remained positive. The PHA titer was therefore a more reliable and more sensitive indicator of immune status against measles than the HI titer. The decrease in PHA titer by 2ME treatment provided evidence of a current or very recent infection. PHA was found to be useful both for assessing immunity status and for serodiagnosis.